Eating behavior-mediated association between attention deficit hyperactivity disorder and body fat mass. Issue 3 (March 2023) - Wu, Dandan; Chen, Shujin; Lin, Shuang; Huang, Rong; Li, Rong; Huang, Yiyang; Chen, Mengying; Li, Xiaonan
Abstract: Background: Adverse eating behaviors and a high rate of obesity have been identified among children diagnosed with attention deficit hyperactivity disorder (ADHD). In this study, we investigate the relationships between eating behaviors and body fat mass among children with ADHD. Methods: All participants were recruited from the Children's Health Care Department of the Children's Hospital of Nanjing Medical University from June 2019 to June 2020. ADHD was diagnosed according to the diagnostic criteria of the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) by psychiatrists. Core ADHD symptoms defined by the DSM-5 were inattention and hyperactivity/impulsivity. The anthropomorphic indices defined by the World Health Organization (WHO) were utilized in this study (body mass index [BMI], underweight, normal body mass, overweight, obesity, short stature). Body fat mass, fat mass percentage (FM%), skeletal muscle mass, skeletal muscle mass percentage (SMM%) were tested via body composition meter, and eating behaviors were assessed by parents using the Chinese version of the Children's Eating Behavior Questionnaire (CEBQ). The CEBQ was comprised of subscales related to food avoidant behaviors (satiety responsiveness, slowness in eating, fussiness, and emotional undereating) and food approach behaviors (food responsiveness, enjoyment of Food, desire to drink, and emotional overeating). The associations among ADHD, obesity and adverse eating behavior were tested through correlation analysis, and a mediating effect model was established to explore the effect of eating behaviors. Results: A total of 548 participants aged 4–12 years were recruited. Among them, 396 were diagnosed with ADHD, with the remaining 152 enrolled in a control group. Compared with the control group, the ADHD group had higher incidences of overweight (22.5% vs. 14.5%) and obesity (13.4% vs. 8.6%) (p < 0.05). The ADHD group was more likely to display "slowness in eating" (11.01 ± 3.32 vs. 9.74 ± 2.95), "fussiness" (15.61 ± 3.54 vs. 15.03 ± 2.84), "food responsiveness" (11.96 ± 4.81 vs. 9.88 ± 3.71) and "desire to drink" (8.34 ± 3.46 vs. 6.58 ± 2.72) (p < 0.05). Moreover, The FM% of children with ADHD was positively correlated with inattention ( β = 0.336, 95% CI : 0.001 to 0.673) and "food responsiveness" ( β = 0.509, 95% CI : 0.352 to 0.665) in the multiple linear regression model. The mediation effect model showed that "food responsiveness" accounted for a significant portion (64.2%) of the mediating effect. Conclusion: Children with ADHD had higher prevalence of overweight and obesity. As an important risk factor, food responsiveness may connect core symptoms of ADHD with obesity.